1992
DOI: 10.1042/bj2840539
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of okadaic acid derivatives on protein phosphatases. A study on structure-affinity relationship

Abstract: The effect of structural modifications of okadaic acid (OA), a polyether C38 fatty acid, was studied on its inhibitory activity toward type 1 and type 2A protein phosphatases (PP1 and PP2A) by using OA derivatives obtained either by isolation from natural sources or by chemical processes. The dissociation constant (Ki) for the interaction of OA with PP2A was estimated to be 30 (26-33) nM [median (95% confidence limits)]. The OA derivatives used and their affinity for PP2A, expressed as Ki (in brackets) were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
170
1
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(186 citation statements)
references
References 26 publications
14
170
1
1
Order By: Relevance
“…The importance of the hydrogen bond between Tyr-272 and the acid group of OA is exemplified by the observation that esterification or removal of the acidic moiety in OA results in elimination of its inhibitory activity and by the fact that mutation of Tyr-272 to Phe results in a 50-fold increase in the K i value (20,22). Despite the intimate interaction of the C-2 hydroxyl group of OA with the Arg-96 side chain, removal of the hydroxyl group results in only a 7-fold increase in the K i value (24). In contrast, mutation of Arg-221 to Ser confers resistance to inhibition by OA, underlining the importance of the interaction between the Arg and the C-24 hydroxyl of OA (25).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the hydrogen bond between Tyr-272 and the acid group of OA is exemplified by the observation that esterification or removal of the acidic moiety in OA results in elimination of its inhibitory activity and by the fact that mutation of Tyr-272 to Phe results in a 50-fold increase in the K i value (20,22). Despite the intimate interaction of the C-2 hydroxyl group of OA with the Arg-96 side chain, removal of the hydroxyl group results in only a 7-fold increase in the K i value (24). In contrast, mutation of Arg-221 to Ser confers resistance to inhibition by OA, underlining the importance of the interaction between the Arg and the C-24 hydroxyl of OA (25).…”
Section: Discussionmentioning
confidence: 99%
“…Usually, MeOk has been considered as an inactive molecule because of its low activity in inhibiting PPs (Nishiwaki et al, 1990;Takai et al, 1992). However, recent studies indicated that MeOk induced reorganization of the actin cytoskeleton of human neuroblastoma cells (Vilarino et al, 2008), and although the potency of MeOk was lower than that of OA, its mechanism of action was unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Methyl okadaate (MeOk) is a methyl ester derivative of the OA, artificially produced in the laboratory, but also found in shellfish, and even in naturally collected or cultured dinoflagellates from the genera Prorocentrum and Dinophysis (Hu et al, 1992;Vale and Sampayo, 1999;Suzuki et al, 2004;Suarez-Gomez et al, 2005). Usually, MeOk has been considered as an inactive molecule because of its low activity in inhibiting PPs (Nishiwaki et al, 1990;Takai et al, 1992). However, recent studies indicated that MeOk induced reorganization of the actin cytoskeleton of human neuroblastoma cells (Vilarino et al, 2008), and although the potency of MeOk was lower than that of OA, its mechanism of action was unknown.…”
mentioning
confidence: 99%
“…Interestingly, a high concentration of okadaic acid was needed to aect Aurora2 activity. At this concentration okadaic acid inhibits both protein phosphatases PP2A and PP1 together, while at lower concentrations only PP2A would be inhibited (Takai et al, 1992).…”
Section: Okadaic Acid Treatment Induces Phosphorylation Of Aurora2 Onmentioning
confidence: 99%